Elevation in 5‐FU‐induced apoptosis in Head and Neck Cancer Stem Cells by a combination of CDHP and GSK3β inhibitors. (28th August 2014) - Shigeishi, Hideo; Biddle, Adrian; Gammon, Luke; Rodini, Camila O.; Yamasaki, Miho; Seino, Sayaka; Sugiyama, Masaru; Takechi, Masaaki; Mackenzie, Ian C.
Abstract : Background: Cancer stem cells (CSCs) are involved in both tumourigenesis and in tumour recurrence after therapy. In head and neck squamous cell carcinoma (HNSCC), there are two biologically different CSC phenotypes both of which express high levels of CD44 but differ in their expression levels of epithelial‐specific antigen (ESA). One phenotype is CD44 high /ESA high and has epithelial features (Epi‐CSCs), while the other is CD44 high /ESA low, has undergone epithelial to mesenchymal transition (EMT‐CSCs), has mesenchymal features and is migratory (Biddle et al., 2011). CSCs are resistant to therapeutically induced apoptosis but the molecular mechanisms by which they develop apoptotic resistance remains unclear. However, glycogen synthase kinase 3β (GSK3β) contributes to regulation of both the self‐renewal and switching of these two CSC phenotypes (Shigeishi et al., 2013). Methods: CD44 high /ESA low, CD44 high /ESA high and CD44 low cells were FACS sorted from the HNSCC cell line LUC4, and 5‐FU‐induced apoptosis was analysed by Annexin V staining followed by flow cytometry analysis. Results: CD44 high /ESA low cells exhibited marked resistance to 5‐FU‐induced apoptosis and had high expression of dihydropyrimidine dehydrogenase (DPD). The DPD inhibitor, 5‐chloro‐2, 4‐dihydroxypyridine (CDHP) significantly enhanced 5‐FU‐induced apoptosis of CD44 high /ESA low cells. Inhibition of GSK3β induced CD44 high /ESA low cells to undergo mesenchymal‐to‐epithelial transition (MET) to CD44 high /ESA high cells and pre‐existing CD44 high /ESA high cells to differentiate. Apoptosis induced by 5‐FU was thus facilitated. Combination of both CDHP and GSK3β inhibitors markedly enhanced 5‐FU‐induced apoptosis of CD44 high /ESA low cells. Conclusions: Our results suggest potentially new approaches for the elimination of the therapy resistant HNSCC CSC population.